Peningkatan Aktivitas dan Hasil Belajar Siswa Melalui Pembelajaran Kooperatif Tipe Numbered Head Together Pada Materi Pola Perilaku Konsumen dan Produsen Dalam Kegiatan Ekonomi - Shobirin, Shobirin (Jurnal Indonesia Sosial Sains, 2022)
The purpose of the study was to determine the increase in student activity and learning outcomes in Economics learning in Class X.3 Social Studies at SMA Negeri 1 Lohbener Indramayu in the academic year 2021/2022 odd semester taught with Numbered Head Together (NHT) cooperative learning and to determine the impact of the Numbered Head method. Together (NHT) in improving the activities and learning outcomes of Class X.3 Social Studies students of SMA Negeri 1 Lohbener Indramayu in the 2021/2022 academic year on the subject of Consumer and Producer Behavior Patterns in economic activities. The research design and method used a classroom action research pattern with .30 students as research subjects in class X.3 Social Studies. Increased student activity in the economics learning process can be seen in the following things; 1) Student activity in the Economics learning process is quite high, because even though it has not reached the specified criteria, namely 85% of students are actively involved, there is an increase in each cycle. 2) The group of students has a high interest in the learning process, because it exceeds the specified criteria, which is 83.33% exceeding the specified criteria of 75%. 3) Students have high attention in the learning process because they have exceeded the specified criteria, which is 87.5%, far beyond the set criteria of 75%. 4) Students have a very high participation in the learning process because they have exceeded the criteria set, namely 91.67%, far exceeding the criteria set at 75%. 5) Students have the ability to do a very high percentage because they have exceeded the criteria set, namely 95.83%, far exceeding the predetermined criteria of 75%.